Chronic stress modulates the expression level of leptin and leptin receptors in the hypothalamus of male rats with a history of maternal stress - Roya Hosseini; Sara Emadian; Manijeh Dogani; Touba Ghazanfari; Nayere Askari (Brain, Behavior, & Immunity - Health)
The activity of different neurotransmitter pathways in the hypothalamus controls the stress response. Meanwhile, leptin is known as an effective mediator in the stress response, and its serum and brain levels change when exposed to stressful factors. In this study, the effect of chronic social instability stress (INS) and chronic unpredictable stress (CUS) on anxiety-like behavioral responses and the level of expression of leptin and its receptor in the brain of male Wistar rats that were under maternal stress (MS) were investigated. Grouping: control (n = 7), MS (n = 7), INS (n = 7), CUS (n = 7), MS + INS (n = 7), MS + CUS (n = 7). Forced swimming, elevated plus-maze, and open field tests were used to check anxiety-like behaviors. Next, the mRNA expression of leptin and its receptor in the hypothalamus was measured by Real-Time PCR. According to the results, adult rats with maternal stress showed an increase in their anxiety-like behaviors faced with the stress of chronic social instability and chronic unpredictable stress (compared to the groups that only received adult stresses). Also, the hypothalamic expression of leptin decreased, but we saw an increase in the expression of hypothalamic leptin receptors in INS, CUS, and MS groups and a decrease in MS + INS and MS + CUS groups. Results of this research suggest that leptin plays a role as an effective mediator in the occurrence of central and behavioral changes caused by maternal stress. In other words, it can be effective in changing resilience in the face of adult stress.